FAKTOR RISIKO KEGEMUKAN PADA WANITA DEWASA INDONESIA - Rian Diana; Indah Yuliana; Ghaida Yasmin; Hardinsyah Hardinsyah (Jurnal Gizi dan Pangan, 2013)
This study was aimed to analyze risk factors of overweight women aged 19—55 years in Indonesia. This study used electronic files data of the National Basic Health Research 2010 from Ministry of Health, which was designed as a cross sectional survey. A total of 57,167 women aged 19—55 years were selected for the analysis. A logistic regression was applied to analyze risk factors of overweight. The result showed that 29.4% of subjects were overweight (including obese). The significant risk factors (p<0.05) of overweight among subjects were marital status (OR for married=2.712; 95%CI:2.559—2.875), household income (OR for high income=1.566; 95%CI:1.504—1.631), living settlement (OR for urban=1.358; 95%CI:1.304—1.413), physical activity (OR for sedentary=1.213; 95%CI:1.153—1.275), energy from carbohydrate (EAC) (OR for EAC≥55%=1.119; 95%CI:1.067—1.173), and energy from sugary sweetened foods (ESF) (OR for ESF≥10%=1.100; 95%CI:1.037—1.166). Education level (OR for higher education=0.817; 95%CI:0.782—0.853) was a protective factors for overweight. This implies the importance of promoting physical activity and healthy diet, especially with sugary sweetened foods and adequate energy from carbohydrate, for preventing and controlling overweight among Indonesian adults especially women.